CLINICAL AND MORPHOLOGICAL CHARACTERISTICS OF SOME JAW CYSTS - Tkachenko, P.I.; Starchenko, I.I.; Belokon, S.A.; Prilutskiyi, K. (World of Medicine and Biology, 2013)
The article based on the study of the morphological structure of jaws of human fetuses at 10-30 weeks of fetal development, describes entities that may later become the source of some of the clinical entities of cystic lesions of the jaw bones. These assumptions to some extent confirmed by clinical and morphological features of mentioned cysts.